Kemampuan Mengucapkan Kosa Kata Umum Pada Anak Usia Dini - Jafarudin Jafarudin; Chairan Zibar L.Parisu; Waode Eti Hardiyanti (Jurnal Sultra Elementary School, 2020)
The purpose of this study was to analyze the ability to pronounce common vocabulary among early childhood students at TK Putri Ananda. This research employed a quantitative descriptive design. The subjects of the study were 34 students, consisting of 18 boys and 16 girls. The instruments used were observation, interviews, and documentation. The data were analyzed using quantitative descriptive analysis. The results of the study revealed that girls had a higher ability to pronounce common vocabulary than boys. Furthermore, two children were found to have not yet been able to pronounce common vocabulary words perfectly. These findings indicate a difference in vocabulary pronunciation ability between male and female early childhood students at TK Putri Ananda.